Evolutionary significance of exine ultrastructure in the subfamily Barnadesioideae (Asteraceae) in the light of molecular phylogenetics - Tellería, María Cristina (2015)
Barnadesioideae (94 species) is the sister subfamily to the rest of the Asteraceae (23,000 species). Pollen grains in this subfamily are structurally and sculpturally distinctive and diverse. Although pollen morphology has contributed to the taxonomy of the subfamily, there is a gap of knowledge concerning the evolution of the exine structure. This study aims at exploring the systematic and phylogenetic significance of optimizing selected pollen characters of Barnadesioideae on the latest molecular phylogenetic tree. Transmission electron microscope (TEM) observations on pollen of selected species, some of them never explored so far, show that the exine probably evolved from a thin pattern (ca. 1–3 μm), with a well-developed foot layer and solid and free columellae, present in sister family Calyceraceae, towards a thicker (> 6–11 μm) and a more complex columellate-granulate bilayered exine in Barnadesioideae (with very delicate columellae). The particular exine structure observed in the monotypic Schlechtendalia luzulaefolia, which combines compact and independent columellae (common in more derived Asteraceae) with a granular internal tectum as the inner ectexine layer (as in Barnadesioideae), reinforces its distant phylogenetic position within Barnadesioideae. More derived lineages within Asteraceae (e.g. Mutisioideae) retained some ancestral exine features although evolved an even thicker exine and a columellate trilayered exine (with robust columellae), rare in the angiosperm pollen grains.